Analiza pogledov Nemškega združenja za zakonodajo - Igličar, Albin (Pravni letopis, 2012)
The State governed by the rule of law can also explicitly and directly orientate legislative activity. Then orientating legal development is a responsible political and legal action. In it elements of politics and interest intermingle with professional and legal ones. Setting legal goals and defining legal remedies for achieving these goals is the essence of legal policy. We use rules and procedures of nomothetics in legal standardisation of social relations. Together with jurisprudence and the disciplines of philosophy of law and sociology of law also nomotechnics must help in its way to determine the circle of social relations to be legally standardised. Legislative procedure, like other legally regulated processes, is based on some relatively permanent principles included in the legal system. Such principles facilitate the use and interpretation of provisions of standing orders referring to the course of legislative procedure in the parliament. The principles are particularly useful in new situations which can never be legally regulated in advance to the last detail, so that it is possible to solve them later by means of creative use of written rules of procedure and its principles.
Keywords: nomotehnika; pravna država; pravno normiranje; zakonodaja; zakonodajni postopek